Organizational Strategies for Enhancing Employee Well-Being: A Flexible and Personalized Approach in the Digital Era - Pratama, Hendra Bayu; Sari, Intan Melati (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2025)
The new digital age calls for organizations to focus not just on productivity but also on employees' well-being and the perks that come with it. The increasing demand for work flexibility and the customization of well-being programs have become serious factors in talent attraction and retention. This research aims to analyze how organizational strategies for work flexibility and individualized well-being programs positively affect employee well-being in the digital era, with a focus on Indonesia. The study proceeded by conducting a survey of 400 employees from digital-based companies against predetermined criteria using a quantitative methodology. The instrument that comprised the questionnaire was structured using a Likert scale. After being tested for validity and reliability, the data were analyzed using multiple linear regression. From the results, we find that both work flexibility and personalization have significant and positive effects on employee well-being, with personalization exerting a greater effect (β=0.428) than flexibility (β=0.312). Therefore, the two variables account for 53.2% of the variance in employee well-being. This study's contribution lies in combining flexibility and personalization into a more holistic organizational strategy, which has not been much investigated in the Indonesian context. In practice, organizations should complement their flexible policies with well-being programs based on individual employee needs to improve retention, loyalty, and sustainable performance.